11.5k views
3 votes
-4x +4 - 12x combining like terms?​

User Axxelsian
by
5.4k points

2 Answers

5 votes

Answer:

-16x+4

Explanation:

4 is the only constant term there dont have to change

-4x-12x =-16x

so you get -16x+4

User Zaur
by
5.5k points
1 vote

Hey there!

-4x + 4 - 12x

COMBINE the LIKE TERMS

= (-4x - 12x) + (4)

= -4x - 12x + 4

= -16x + 4

Therefore, your answer should be:

-16x + 4


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User Christoph Adamakis
by
5.3k points